Integrating nutrition security with treatment of people living with HIV: Lessons from Kenya - Bryan, Elizabeth; Gillespie, Stuart; Nangami, Mabel (SAGE Publications, 2008)
The increased caloric requirements of HIV-positive individuals, undesirable side effects of treatment that may be worsened by malnutrition (but alleviated by nutritional support), and associated declines in adherence and possible increased drug resistance are all justifications for developing better interventions to strengthen the nutrition security of individuals receiving antiretroviral treatment. To highlight key benefits and challenges relating to interventions aimed at strengthening the nutrition security of people living with HIV who are receiving antiretroviral treatment.Qualitative research was undertaken on a short-term nutrition intervention linked to the provision of free antiretroviral treatment for people living with HIV in western Kenya in late 2005 and early 2006.Patients enrolled in the food program while on treatment regimens self-reported greater adherence to their medication, fewer side effects, and a greater ability to satisfy increased appetite. Most clients self-reported weight gain, recovery of physical strength, and the resumption of labor activities while enrolled in dual (food supplementation and treatment) programs. Such improvements were seen to catalyze increased support from family and community. These findings provide further empirical support to calls for a more holistic and comprehensive response to the coexistence of AIDS epidemics with chronic nutrition insecurity. Future work is needed to clarify ways of bridging the gap between short-term nutritional support to individuals and longer-term livelihood security programming for communities affected by AIDS. Such interdisciplinary research will need to be matched by intersectoral action on the part of the agriculture and health sectors in such environments.